12/15 lipoxygenase: A crucial enzyme in diverse types of cell death. (September 2018) - Li, Qiu-Qi; Li, Qin; Jia, Ji-Ning; Liu, Zhao-Qian; Zhou, Hong-Hao; Mao, Xiao-Yuan
Abstract: The 12/15-lipoxygenase (12/15-LOX) enzymes react with polyunsaturated fatty acids producing active lipid metabolites that are involved in plethora of human diseases including neurological disorders. A great many of elegant studies over the last decades have contributed to unraveling the mechanism how 12/15-lipoxygenase play a role in these diseases. And the way it works is mainly through apoptosis. However, recent years have found that the way 12/15-lipoxygenase works is also related to autophagy and ferroptosis, a newly defined type of cell death by Stockwell's lab in 2012. Figuring out how 12/15-lipoxygenase participate in these modes of cell death is of vital importance to understand its role in disease. The review aims to give a sight on our current knowledge on the role of this enzyme in apoptosis, autophagy and ferroptosis. And the relevant diseases that 12/15-lipoxygenase may be involved. Highlights: 12/15-lipoxygenase plays a key role in apoptosis. 12/15-lipoxygenase is involved in the newly discovered types of cell death including autophagy and ferroptosis. 12/15-lipoxygenase tends to be a potent drug target.